Biochemical properties of a high fidelity DNA ligase from Thermus species AK16D. - Tong, J (1999)
NAD+-dependent DNA ligases from thermophilic bacteria Thermus species are highly homologous with amino acid sequence identities ranging from 85 to 98%. Thermus species AK16D ligase, the most divergent of the seven Thermus isolates collected worldwide, was cloned, expressed in Escherichia coli and purified to homogeneity. This Thermus ligase is similar to Thermus thermophilus HB8 ligase with respect to pH, salt, NAD+, divalent cation profiles and steady-state kinetics.However, the former is more discriminative toward T/G mismatches at the 3'-side of the ligation junction, as judged by the ratios of initial ligation rates of matched and mismatched substrates. The two wild-type Thermus ligases and a Tth ligase mutant (K294R) demonstrate 1-2 orders of magnitude higher fidelity than viral T4 DNA ligase. Both Thermus ligases are active with either the metal cofactor Mg2+, Mn2+or Ca2+but not with Co2+, Ni2+, Cu2+or Zn2+. While the nick closure step with Ca2+becomes rate-limiting which results in the accumulation of DNA-adenylate intermediate, Ni2+only supports intermediate formation to a limited extent. Both Thermus ligases exhibit enhanced mismatch ligation when Mn2+is substituted for Mg2+, but the Tsp. AK16D ligase remains more specific toward perfectly matched substrate.